Regulations regarding living organ donation in Europe : possibilities of harmonisation - Lopp, Leonie (Springer Berlin Heidelberg, 2013)
Organ transplantation is a much-discussed subject, and the importance of living organ donation is increasing significantly. Yet despite all efforts, too few donor organs are available to help all patients in need. This book analyses whether the national legal regulations are also partly responsible for the organ shortage in the Member States of the European Union. In addition to a detailed analysis of the various national regulations, the main arguments in favour of and against legal restrictions on living organ donation are considered. Furthermore, the European Union's authority is investigated, namely, whether it is entitled to establish statutory provisions for the Member States with respect to a harmonized regulation of living organ donation. Based on the results of the analysis, the author establishes a Best Practice Proposal for living organ donation.